Regulation of Notch and Wingless signalling by phyllopod, a transcriptional target of the EGFR pathway. - Nagaraj, R.; Banerjee, U. (The EMBO Journal, 2009)
Spatial and temporal control of Notch and Wingless (Wg) pathways during development is regulated at multiple levels. Here, we present an analysis of Phyllopod as a coordinated regulator of these two critical signal transduction pathways. Phyl specifically helps traffic Notch and Wg pathway components within early endocytic vesicles, thereby controlling the amount of processed signal available for causing a transcriptional response within the nucleus. In Drosophila, the EGFR pathway transcriptionally activates phyl whose product then blocks Notch and Wg signalling pathways. This provides a mechanistic basis for an antagonistic relationship between receptor tyrosine kinase and Notch/Wg pathways during development. Furthermore, this study identifies a Phyl-regulated class of endosomal vesicles that specifically include components of Notch and Wg signalling.